Genetic potential of rice under alternate-wetting-and-drying irrigation management for barnyardgrass (Echinochloa crus-galli) suppression and grain yield production. Issue 4 (July 2019) - Gealy, David R.; Rohila, Jai S.; Boykin, Deborah L.
Abstract: Barnyardgrass [ Echinochloa crus-galli (L.) P. Beauv.] is one of the most troublesome and competitive weed species in rice ( Oryza sativa L.) grown under conventional flood (FLD) irrigation and is expected to be similarly damaging under alternate-wetting-and-drying (AWD) irrigation. Several indica rice genotypes have been shown to suppress E. crus-galli under FLD management, but very little is known about the nature and potential of weed suppression using AWD irrigation. In this 3-yr field study, we evaluated seven diverse rice genotypes for their weed suppression and grain yield potential under FLD and AWD irrigation. The E. crus-galli dry biomass at midseason was 11% less under AWD compared with FLD. Overall, plots of an indica variety and a hybrid resulted in less E. crus-galli dry biomass under AWD compared with FLD. Grain yield in weed-free AWD plots averaged 12% less than in weed-free FLD plots. Grain yield of the tropical japonica (TRJ) type, 'Bengal', was 32% lower under AWD than FLD, whereas grain yields of the two indica genotypes, PI 312777 and 'Rondo', and a hybrid were similar in both irrigation systems. Grain yield reduction in E. crus-galli –infested AWD plots averaged greater than 90%. Thus, E. crus-galli greatly reduced the grain yield of all rice genotypes tested in both FLD and AWD systems in this study. Grain yield of the indica and hybrid genotypes was relatively less affected by the AWD treatments compared with the TRJ genotypes, particularly with Bengal, suggesting that the weed-suppressive genotypes, PI 312777 and Rondo, would be better suited to AWD irrigation systems and for inclusion in weed-suppression rice-breeding programs in the southern United States.